Assessment of Occupational Noise Exposure in Industrial Environments: A Case Study in Metal Casting - Annisa Restia Dwiandra; Qurtubi; Haswika Haswika; Muchamad Sugarindra (Advance Sustainable Science Engineering and Technology, 2025)
Good work environment conditions can affect the increase in worker productivity. One of the work environment factors that needs to be considered is distraction. Noise problems not only interfere with concentration but can also damage workers' hearing and reduce overall work safety. Therefore, this study aims to analyze the noise level in the work area in the production process of a company engaged in the metal casting industry and provide recommendations that can reduce the negative impact on the workforce. This measurement uses Decibel X with a time interval of five seconds, and then data processing is carried out to determine the LTm5 value. The measurement results show that the level of disturbance in some work areas exceeds the recommended threshold, increasing the risk of worker health problems. To reduce this negative impact, the study provides the provision of personal protective equipment (PPE), such as earplugs, as well as the implementation of occupational safety and health (OHS) socialization. This research makes an essential contribution to the management of nuisance risks in industrial environments, especially in improving worker safety and health through effective mitigation strategies.